Parametric study of irreversible electroporation with different needle electrodes: Electrical and thermal analysis. (August 2014) - Nickfarjam, Abolfazl; Firoozabadi, S. Mohammad P.
Abstract Purpose: Irreversible electroporation (IRE) is a new tumour ablation method used in cancer treatment procedures. In a successful IRE treatment it is crucial to impose minimum thermal damage to the tumour and its surrounding healthy tissue, while subjecting the entire tumour to a strong electric field. Method: Here we present a 3D model of a subcutaneous tumour in a four-layer skin using a geometry-based finite element approach. Four common needle electrode configurations were studied in this paper. The study evaluated six essential factors which are important in the electrical and thermal distributions in tumour and normal tissue. Results: The results revealed that a hexagonal 3 × 3 geometry provides the maximum electrical coverage of the tumour, compared to other electrode configurations. However, in some cases the hexagonal 2 × 2 geometry can ablate the entire tumour with less damage to normal tissue. We found that the deeper insertion of 2- and 4-electrode geometries can lead to more damage to healthy tissue. The results also indicate that the insertion of the electrodes into tumour tissue can increase thermal damage dramatically due to existing large electrical conductivity. Conclusion: These findings suggest that needle electrodes should not be placed within the tumour tissue if the goal is to prevent thermal damage. This method can be used as a trade-off between electric field coverage in tumour tissue and thermal damage to both tumour and normal tissue.